2018
DOI: 10.1002/ptr.6014
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Tanshinone IIA combined with Taxol on drug‐resist breast cancer cells MCF‐7 through inhibition of Tau

Abstract: Drug resistance represents a major obstacle to improving the overall response and survival of cancer patients. Taxol is one of the most commonly used chemotherapy agents in breast cancer. As with many cancer therapeutic agents, resistance remains a significant problem when using Taxol to treat malignancies. In this study, estrogen receptor positive breast cancer cells MCF-7 were induced Taxol resistance. And Tanshinone IIA combined with Taxol was chosen to treat it. The drugs combination showed additive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Tanshinone IIA (Tan IIA), an effective active ingredient of Salvia miltiorrhiza, is often used clinically for the treatment of ischemic heart disease because of its pharmacological actions such as improving coronary circulation (Jiang et al, ), lowering blood lipids (Kang et al, ), inhibiting platelet aggregation and thrombus formation (Li, Yang, & Zhao, ), retarding development of arteriosclerosis (Adams, Wang, Yang, & Lien, ), decreasing inflammatory reaction (Fan et al, ), and etc. In addition, many studies have shown that Tan IIA has antitumor effects and can kill a variety of cancer cells, including breast cancer cells (Lin et al, ), gastric cancer cells (Chen, Shi, Liu, & Zhong, ), colon cancer cells (Liu et al, ), prostate cancer cells (Won et al, ), and etc. Because one of the main toxic side effects of Dox is cardiotoxicity, and TanIIA not only has antitumor activity but also cardiovascular protective effect, therefore, we combined Dox with Tan IIA to assess the effect of Tan IIA on the toxic side effects of Dox while evaluating its effect on the anti‐breast cancer activity of Dox and to investigate the possible mechanism of the effect of Tan IIA on the anti‐breast cancer activity of Dox.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanshinone IIA (Tan IIA), an effective active ingredient of Salvia miltiorrhiza, is often used clinically for the treatment of ischemic heart disease because of its pharmacological actions such as improving coronary circulation (Jiang et al, ), lowering blood lipids (Kang et al, ), inhibiting platelet aggregation and thrombus formation (Li, Yang, & Zhao, ), retarding development of arteriosclerosis (Adams, Wang, Yang, & Lien, ), decreasing inflammatory reaction (Fan et al, ), and etc. In addition, many studies have shown that Tan IIA has antitumor effects and can kill a variety of cancer cells, including breast cancer cells (Lin et al, ), gastric cancer cells (Chen, Shi, Liu, & Zhong, ), colon cancer cells (Liu et al, ), prostate cancer cells (Won et al, ), and etc. Because one of the main toxic side effects of Dox is cardiotoxicity, and TanIIA not only has antitumor activity but also cardiovascular protective effect, therefore, we combined Dox with Tan IIA to assess the effect of Tan IIA on the toxic side effects of Dox while evaluating its effect on the anti‐breast cancer activity of Dox and to investigate the possible mechanism of the effect of Tan IIA on the anti‐breast cancer activity of Dox.…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone IIA (Tan IIA), an effective active ingredient of Salvia miltiorrhiza, is often used clinically for the treatment of ischemic heart disease because of its pharmacological actions such as improving coronary circulation (Jiang et al, 1981), lowering blood lipids (Kang et al, 2008), inhibiting platelet aggregation and thrombus formation (Li, Yang, & Zhao, 1984), retarding development of arteriosclerosis (Adams, Wang, Yang, & Lien, 2006), decreasing inflammatory reaction (Fan et al, 2009), and etc. In addition, many studies have shown that Tan IIA has antitumor effects and can kill a variety of cancer cells, including breast cancer cells (Lin et al, 2018), gastric cancer cells (Chen, Shi, Liu, & Zhong, 2012), colon cancer cells (Liu et al, 2013), prostate cancer cells (Won et al, 2010)…”
mentioning
confidence: 99%
“…For example, Tau was shown to regulate the MT-dependent migration of cancer cells (Breuzard et al, 2019). Finally, similar to stathmin, Tau level of expression modulates clinical MT-targeting agent efficiencies, such as taxanes or vinca alkaloids (Rouzier et al, 2005; Li et al, 2013; Smoter et al, 2013; Malesinski et al, 2015; Lin et al, 2018).…”
Section: Perspectivesmentioning
confidence: 99%
“…Clinically, the patients with PTX chemoresistance show over expression of MAPT significantly [24]. Identification of MAPT inhibitors and their use in cancer treatment along with PTX improve the treatment results in the either case, PTX sensitive and resistant tumor [25,26].…”
Section: Introductionmentioning
confidence: 99%